Balanced Growth Finding Strategies for Sustainable Development - Mennillo, Giulia; Schlenzig, Thomas; Friedrich, Elmar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
What is balanced growth? This book shows that the definitions and implications of the concept of balanced growth vary significantly among the different disciplines in economic science, but are not exclusive at all. Terms such as sustainability or balanced growth have become buzzwords. In practice, they are often a desirable vision rather than an achievable objective. Why? Doubts may arise about the extent to which such concepts are compatible with a modern market economy. Is balanced growth possible at all? Is it reasonable to accept balanced growth as a norm? Why should a balanced growth path be a desirable strategy to pursue for policymakers, managers, employees, and other societal stakeholders? Empirical evidence suggests that the actual worldwide economic growth is not balanced at all. Meanwhile, ever since the beginning of the financial and economic crisis in 2007 and its accompanying spillover effects, our globalizing world has uncompromisingly shown the flip side of its coin. Its crisis-prone character has intensified the discussion about our economic system$1 (Bs sustainability. Questions related to acceptable sovereign debt levels, suitable trade deficits and surpluses, firms$1 (Bgrowth targets, resource management and efficiency have aroused high interest. What is the cause of the observed imbalances? In our opinion, this debate must involve rethinking the qualitative and quantitative dimension of our present understanding of the nature of economic growth. This book accompanies the 9th DocNet Management Symposium of the University of St. Gallen, Switzerland. It contains contributions of the symposium's panel speakers, renowned authors to the field and young researchers. The Ph.D. students$1 (Band post-doctoral association DocNet organizes the DocNet Management Symposium on a yearly basis with the goal to foster exchange between academia and practitioners.s
Balanced Growth - the economic perspective -- Balanced Growth - a business perspective -- Balanced Growth - a resource management perspective.
Keywords: Economics; Environmental economics; Industrial management; Economics/Management Science; Non-Profit Enterprises/Corporate Social Responsibility; Management/Business for Professionals; Energy Policy, Economics and Management; Environmental Economics